Biochemical and immunological properties of excretory-secretory antigen Opisthorchis felineus (Experimental biology, 2016)
The main component at statement of serological reactions is an antigen, which should have the necessary biochemical and immunological properties, high specificity and activity. The article presents data on the production of excretory-secretory antigens of the Opisthorchis felineus pathogen. Describes a scheme for obtaining an antigenic product which is obtained by culturing Opisthorchis pathogens in vitro in the RPMI-1640 synthetic medium and further purified by centrifugation. Comparable experiments for the detection of protein antigen components show advantage silver staining method over the standard method, which is based on using Coomassie solution. Considering this fact, by its author has been proven that in the excretory-secretory antigen includes up to 21 of the protein fraction. The article presents data on the study of activity, specificity and immunogenicity of excretory-secretory antigen. Using the antigen in indirect ELISA version with sera of infected dogs showed its high activity and the possibility of applying for the detection of specific antibodies against the opisthorchiasis pathogen. In addition, the use of said antigen for immunization of laboratory mice and Syrian hamsters showed high immunological activity of antigen and ability to induce an immune response in the organism of laboratory animals.
Keywords: immunology; Opisthorchis felineus; a marita; excretory-secretory antigen; electrophoresis; immunogenicity.